2019
DOI: 10.1038/s41422-019-0229-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial CDS2 deficiency causes VEGFA-mediated vascular regression and tumor inhibition

Abstract: The response of endothelial cells to signaling stimulation is critical for vascular morphogenesis, homeostasis and function. Vascular endothelial growth factor-a (VEGFA) has been commonly recognized as a pro-angiogenic factor in vertebrate developmental, physiological and pathological conditions for decades. Here we report a novel finding that genetic ablation of CDP-diacylglycerol synthetase-2 (CDS2), a metabolic enzyme that controls phosphoinositide recycling, switches the output of VEGFA signaling from prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 93 publications
2
30
0
Order By: Relevance
“…We hypothesized that FGF2 and HGF protein levels were decreased in OC-2 KO cell lines, which in turn inhibited the activation of HIF-1α to some extent. Then, the expression of VEGFA, the strongest pro-angiogenic growth factor, was down-regulated, destroying the angiogenesis networks ( 40 ). Importantly, the results of the qRT-PCR assay merely indicated that OC-2 positively regulated the expression of VEGFA, FGF2, HGF, and HIF-1α at the transcriptional level, but the accurate relationships among OC-2 and these pro-angiogenic growth factors required further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that FGF2 and HGF protein levels were decreased in OC-2 KO cell lines, which in turn inhibited the activation of HIF-1α to some extent. Then, the expression of VEGFA, the strongest pro-angiogenic growth factor, was down-regulated, destroying the angiogenesis networks ( 40 ). Importantly, the results of the qRT-PCR assay merely indicated that OC-2 positively regulated the expression of VEGFA, FGF2, HGF, and HIF-1α at the transcriptional level, but the accurate relationships among OC-2 and these pro-angiogenic growth factors required further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, the small GTPase Rac1, regulator of actin polymerization and cell migration, is required for vessel regression in the zebrafish brain (Chen et al, 2012) and polarized Rac1 subcellular gradients are induced by laminar (15 dyn/cm 2 ) but not disturbed flow in endothelial cells in vitro (Shao et al, 2017). Similarly, phosphoinositide gradients are required for a balanced capillary pruning induced by VEGF since the absence of CDP-diacylglycerol synthase-2 (CDS2), a metabolic enzyme that controls phosphoinositide recycling, in mouse and zebrafish showed increased endothelial cell migration and vessel regression (Zhao et al, 2019). VEGF was considered an essential player in vascular regression occurring after deprivation of VEGF or VEGF-induced signals which led to endothelial cell apoptosis in different tissues and contexts (Meeson et al, 1999;Tang et al, 2004;Baffert et al, 2006).…”
Section: Mechanisms In Blood Flow-driven Capillary Remodelingmentioning
confidence: 99%
“…However, a recent study has shown that VEGF-A also induced vascular degeneration, which was regulated by phosphatidylinositol metabolic cycle controlled by CDP diacylglycerol synthase-2 (CDS2). ECs with mutant CDS2 suppressed vascular degeneration through reverse migration and apoptosis after being stimulated by VEGF-A ( 39 ).…”
Section: Vegf-amentioning
confidence: 99%